Erprobungsraum Theologie: ein Beitrag zur Reformdebatte mit Bezug auf den neuen Studiengang Pioneer Ministry in Jena - Greifenstein, Johannes (Zeitschrift für Theologie und Kirche, 2024)
Unique in Germany, the Jena Faculty of Theology's newly introduced "Pioneer Ministry" course of study and how it has been received within the broader context of transforming theological education are closely examined in this essay. By stimulating self-reflection and exploring how changes to move beyond outmoded approaches and structures can be made, "Pioneer Ministry" breaks new ground in providing the insight and impetus necessary to redefine traditional theology's characteristics and reassert its academic profile.